Does Electricity Supply Matter for Economic Growth in Russia: A Vector Error Correction Approach - Bass, Alexander (International Journal of Energy Economics and Policy, 2018)
In this article we investigate the relationship between electricity consumption and economic growth in Russia. According to the production function of economic growth models, energy supply must be a catalyst of great importance for the economic growth. We investigate this nexus on the example of the Russian data for the period 1990-2017. Using vector error correction approach and granger causality test we aim to detect presence or absence of cointegration in the long run between electricity supply, economic growth and employment rate. Results show that the sampled variables are cointegrated and there exists a long-run relationship between them. Short-run effects analysis show that electricity supply does not significantly affects economic growth. Granger causality test shows that there exist a unidirectional causality running from electricity supply to economic growth and from economic growth to employment. The results show that electricity supply is essential for boosting economic growth in Russia in the long run. Keywords: economic growth, employment, electricity supply, cointegration, Granger causality JEL Classifications: C22, O13, Q14